2021
DOI: 10.1049/elp2.12025
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of magnetostrictive vibration and acoustics in converter transformer

Abstract: The converter transformers are susceptible to more noise and vibration when compared to power transformers due to the presence of DC bias in the DC transmission line. DC bias occurs mostly due to inaccuracies in valve firing resulting in a small residual DC oscillating around zero. Measurement of magnetostriction becomes significant as it influences the vibration and noise from the core. Hence, a magnetostrictive model of a high-voltage DC converter transformer has been developed. This work analyses the vibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…These analyzes lead to a better understanding of the problem. A piece of better knowledge can point to the need of improving the model and/or to a more enlightened choice of the final solution [33]. Still respecting the tolerance reduction around Uk, the diamond white solution is the one closest to Pareto's set of solutions.…”
Section: Optimization Resultsmentioning
confidence: 99%
“…These analyzes lead to a better understanding of the problem. A piece of better knowledge can point to the need of improving the model and/or to a more enlightened choice of the final solution [33]. Still respecting the tolerance reduction around Uk, the diamond white solution is the one closest to Pareto's set of solutions.…”
Section: Optimization Resultsmentioning
confidence: 99%
“…The electric current through the windings is assumed to be evenly distributed throughout the coil, and a single‐phase supply is fed to the HV windings. It is worth noting that the distribution of flux in the core depends upon the magnetic properties of the chosen material 21 . Magnetic shielding is assumed to be present at the box‐shaped boundary of the transformer.…”
Section: Fem‐based Analysis Of Vibration and Acoustic Noisementioning
confidence: 99%
“…Concerning the available literature at the time of the work, the converter transformers are considered to bear higher harmonics content. In an attempt to analyse the behaviour of the converter transformer, authors in Reference 21 successfully modelled the magnetostrictive vibration and acoustics generated in a converter transformer under the influence of DC bias. Despite the significance of harmonics in the behaviour of the converter transformer, there has not been sufficient related research in any of the reported works on converter transformers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations